Evidencia molecular de diferenciación genética e introgresión entre razas de frijol común del acervo andino - Blair, Matthew W.; Díaz, J.M.; Duque E., Myriam Cristina; Hidalgo, R. (2007)
We used the information generated by 29 microsatellite markers in the analysis of 63 common bean (Phaseolus vulgaris) accessions to evaluate clustering and prevalence indices and to determine the similarity and differentiation or introgression among races of the Andean gene pool. We identified three clusters of genotypes which corresponded to the races of the Andean gene pool, i.e. Nueva Granada, Chile and Peru and the existence of introgression between accessions of these three races. Introgression was more common for genotypes in races Chile and Peru , then for the race Nueva Granada.